From pyridinium-based to centrally active acetylcholinesterase reactivators - Korábečný, Jan; Soukup, Ondřej; Doležal, Rafael; Chalupová, Katarína; Nepovímová, Eugenie; Andrš, Martin; Nguyen, Thuy Duong; Jun, Daniel; Musílek, Kamil; Kučerová-Chlupáčová, Marta; Kuča, Kamil (Mini-reviews in medicinal chemistry, 2014)
Organophosphates are used as pesticides or misused as warfare nerve agents. Exposure to them can be fatal and death is usually caused by respiratory arrest. For almost six decades, pyridinium oximes represent a therapeutic tool used for the management of poisoning with organophosphorus (OP) compounds. However, these compounds possess several drawbacks. Firstly, they are inefficient in the restoration of brain acetylcholinesterase (AChE) activity due to a hard blood-brain barrier penetration. Secondly, there is no broad-spectrum AChE reactivator. Lastly, none of the oximes can reactivate "aged" AChE. In this context, uncharged reactivators represent a new hope in a way of increased bioavailability in the central compartment and better therapeutic management of the OP poisoning.
Keywords: zvířata; Organophosphate Poisoning; Animals; Drug Discovery; Cholinesterase Reactivators; Pyridinium Compounds; pyridinové sloučeniny; Humans; objevování léků; Acetylcholinesterase; otrava organofosfáty; lidé; reaktivátory cholinesterázy; acetylcholinesterasa